EMBLEMATISM OF THE VIRGIN MARY MEANINGS OF THE UKRAINIAN BAROQUE - Soletskyi, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Aim. The paper deals with the study of the emblematic forms expression of the Virgin Mary meanings in the literature of the Ukrainian baroque. The author focuses on the definition and description of emblematic arrangements, their structures, semiotic signs. The purpose of the paper is to identify the functionality and structural integrity of iconic-conventional schemes in working out the sacred meanings of the Virgin Mary. Methods. The study employs a systemic approach with genetic, hermeneutic and semiotic methods. The author draws on the scientific philosophy of semiotics and hermeneutics and employs the cognitive theory of literature (cognitive poetics). This is due to the distinctive nature of the study, its subject of inquiry and scope of research. Results. The paper reviews the emblematic meaning models that figure prominently in the mythological experience arrangement, and since the sixteenth century have been “legitimated” by literature, altered into a popular form that denotes a specific type of artistic iconic-conventional modelling with a specific structure, its individual modifications, a register of themes, symbols, images, which, in general, has the features of a particular genre and, at the same time, denotes a special way of metaphysical expression. The functionality of emblematic modelling is also manifested in the theological meanings making. Originality. The paper summarizes the findings of many scholars who have studied the phenomena of emblematic modelling of the Virgin Mary meanings, specifies their forms, individual artistic representations. Practical significance. The paper provides a basis for further studies on meaning modelling processes as well as iconic-conventional syncretism of representation of the Virgin Mary subject-matter. The findings can underpin coursework and graduation theses.